(untitled) (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
Socialization regarding the e-voting system is important to increase public participation because good socialization can increase people’s desire to exercise their right to vote. The aim of the research is to determine the effect of socialization of the e-voting system on community participation in the election of Wali Nagari Durian Kapeh Darussalam. The approach method used is quantitative. The population is all people registered on the permanent voter list and the respondents are people who exercised their right to vote in the wali nagari election. Samples were taken using the proportionate stratified random sampling technique. The results explain that the variable socialization of the e-voting system has a significant effect on community participation which has an R Square of 0,563, which means that the influence of socialization of the e-voting system on community participation is 56%. In this case, the socialization of the e-voting system has a significant influence on community participation in the election of Wali Nagari Durian Kapeh Darussalam